2007
DOI: 10.1080/07060660709507455
|View full text |Cite
|
Sign up to set email alerts
|

Natural occurrence of a partitivirus in the sapstaining fungusCeratocystis resinifera

Abstract: The bisegmented genome of a double-stranded RNA (dsRNA) virus from isolate LG115 of Ceratocystis resinifera, a sapstaining ascomycete fungus, was characterized. The larger segment (dsRNA-1) was 2305 base pairs in length, whereas the smaller one (dsRNA-2) was 2207 base pairs. The positive strand of dsRNA-1 contained an open reading frame (ORF) with the potential to encode a protein of 661 amino acids, and this ORF was closely related to coat proteins (CPs) of previously characterized fungal partitiviruses. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The latter possibility is supported by the inclusion of HmPV-V70 within the HetPV3-related virus clade. Interspecies virus transmission is considered to be a rare phenomenon among mycoviruses; however, Deng and Boland (2007) reported natural transmission of the betapartitivirus Ceratocystis resinifera virus 1 to Ceratocystis polonica. Recently the partitivirus strain Sclerotinia sclerotiorum partitivirus 1 (SsPV1/WF-1) was found to interspecifically transmitted to Sclerotinia nivalis and Sclerotinia minor (Xiao et al, 2014).…”
mentioning
confidence: 96%
“…The latter possibility is supported by the inclusion of HmPV-V70 within the HetPV3-related virus clade. Interspecies virus transmission is considered to be a rare phenomenon among mycoviruses; however, Deng and Boland (2007) reported natural transmission of the betapartitivirus Ceratocystis resinifera virus 1 to Ceratocystis polonica. Recently the partitivirus strain Sclerotinia sclerotiorum partitivirus 1 (SsPV1/WF-1) was found to interspecifically transmitted to Sclerotinia nivalis and Sclerotinia minor (Xiao et al, 2014).…”
mentioning
confidence: 96%
“…Furthermore, Jiang and collaborators (2021) [ 103 ] studied the fungus Aspergillus nidulans , and Moriyama and collaborators (2021) [ 104 ] analyzed the phytopathogen Rosellinia necatrix , the causative agent of root rot, also identifying viral sequences related to this family. Finally, Deng & Boland (2007) [ 105 ] reported viruses belonging to the genus Partiviridae isolated from Ceratocystis resinifera , called named Ceratocystis partitivirus 1 CPV1. This virus has the same characteristics as the virus present in Ceratocystis polonica.…”
Section: Discussionmentioning
confidence: 99%
“…Similar type of occurrence of virus distribution was found from the inclusion of HmPV-V70 (Osaki et al 2002) within the HetPV3-related virus clade (III). Deng and Boland (2007) showed that interspecies natural transmission of the betapartitivirus Ceratocystis resinifera virus 1 to Ceratocystis polonica. Similarly, transmission case with partitiviruses was found in S. sclerotiorum partitivirus 1 (SsPV1/WF-1) to S. nivalis and Sclerotinia minor (Xiao et al 2014).…”
Section: Interspecies Virus Transmission Through Fungal Hyphal Anastomosis and Natural Distributionmentioning
confidence: 99%